Survival of Bradyrhizobium SP. in alternative legume inoculant carriers - Figueiredo, Márcia do Vale Barreto; Stamford, Newton Pereira; Vidor, Caio; Vilar, José Julio; de Oliveira, Emídio Cantídio Almeida (Pesquisa Agropecuaria Brasileira, 1992)
To evaluate the survival of Bradyrhizobium sp. grown in alternative legume inoculant carriers (diatomaceous earth, powdered coconut fiber, dry vinasse, urban waste compost, vermiculite and peat) submitted to different matric water potential (Ym = -0,33, -1,00 e 3,00 bar), an experiment was carried out using the Bradyrhizobium sp. (Clitoria) strain UMKL 58 (Malasia-NIFTAL). Survivals of bacteria were estimated by the number of viable cells using plate counting and plant infection techniques. Samples were taken from the different treatments at intervals of 0; 12; 30; 60; 90; 120; 150; 180 and 2.40 days during incubation. Lower matric water potentials increased growth and survival of Bradyrhizobium sp. as compared with -0,33 bar. Strain viability in the inoculant differed for each carrier, consistent in both plate count and plant infection techniques. Diatomaceous earth was similar to peat (usual carrier on commercial legume inoculant), and evaluated on -3,00 bar showed the best survival (microbial density of 3,6 x 109 viable cells per gram of inoculant), after six months of storage at 5°C.